2018
DOI: 10.1017/s1366728918000639
|View full text |Cite
|
Sign up to set email alerts
|

“My French is rusty”: Proficiency and bilingual gesture use in a majority English community

Abstract: Gestures serve many functions, including aiding language access and message construction, particularly in spatial tasks. Some researchers have argued that gesture frequency is linked to proficiency in bilinguals, although results have been inconsistent. We tested Nicoladis’ (2007) proposal that bilinguals’ proficiency interacts with task: namely, more spatial tasks elicit greater proficiency effects. French–English bilinguals completed a cartoon-retell task (high spatial) and an interview task (low spatial) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…Recall that gestures can sometimes be used to help access words (Krauss & Hadar, 1999). A follow-up study in the same region of Canada found some support for this interpretation (Aziz & Nicoladis, 2018). In this study, measures of proficiency in French and English showed no relationship with gesture production; however, English-French bilinguals, those who had learned French after learning English, showed significantly greater use of representational gestures in French than in English.…”
Section: Gesture Production and Language Proficiencymentioning
confidence: 50%
See 1 more Smart Citation
“…Recall that gestures can sometimes be used to help access words (Krauss & Hadar, 1999). A follow-up study in the same region of Canada found some support for this interpretation (Aziz & Nicoladis, 2018). In this study, measures of proficiency in French and English showed no relationship with gesture production; however, English-French bilinguals, those who had learned French after learning English, showed significantly greater use of representational gestures in French than in English.…”
Section: Gesture Production and Language Proficiencymentioning
confidence: 50%
“…Proficiency-how well bilinguals know each language-is a multidimensional and complex construct (Silva-Corvalán & Treffers-Daller, 2016). One recent study showed that it may not be so much proficiency but day-to-day usage that predicts gesture frequency in bilinguals (Aziz & Nicoladis, 2018). In other words, gesture frequency will tend to increase if bilinguals do not have opportunities to use a language on an everyday basis.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The data for this study were originally collected to address different research questions to the current ones, including the timing of gestures to speech [14], how gesture use relates to language proficiency [48], and how the use of gestures relates to working memory [49]. None of the present analyses reproduce those that were carried out previously.…”
Section: This Studymentioning
confidence: 99%
“…Studies have shown that the iconic gesture rate was positively correlated with the number of word types for native French speakers (Nicoladis et al, 2009 ), with the number of word tokens for native English speakers (Smithson et al, 2011 ), and with the number of scenes (Laurent et al, 2015 ) and the length of utterances (Nicoladis et al, 1999 ) for bilingual kids; but it had no relationship with the number of word tokens for Chinese-English or French-English bilinguals (Smithson et al, 2011 ), with the number of word types for English native speakers (Nicoladis et al, 2009 ) or English-French bilinguals (Nicoladis et al, 2009 ; Laurent et al, 2015 ), or with the speech rate for either native or bilingual speakers (Smithson et al, 2011 ). In addition, the number of word tokens could predict the iconic gesture rate for Spanish, English, and French native speakers (Nicoladis et al, 2016 ), but the speech rate could not predict it for bilinguals (Aziz and Nicoladis, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both native and highly proficient speakers are less likely to find speech tasks challenging, in which case their available working memory resources are adequate for the task and their gestures are mainly a reflection of their speaking styles (Nagpal et al, 2011 ). On the other hand, less proficient L2 speakers' gesture use has closer association with speech since they need strategies like gesturing to compensate for the shortage of working memory resources during speaking (Nicoladis et al, 2007 ; Aziz and Nicoladis, 2019 ). For example, Nicoladis et al ( 2007 ) found that the positive correlation between the iconic rate and the number of scenes described only held for intermediate Chinese English learners but not for native Chinese speakers.…”
Section: Introductionmentioning
confidence: 99%